POLICY STUDY IN INDONESIA’S PATENT LEGAL SYSTEM - V. Henry Soelistyo Budi (LAW REFORM, 2019)
The Indonesian Patent Law, which was first drafted in 1989, is quite a controversial. As a legal instrument, the Patent Law strongly reflects the monopolistic character. In fact, it raises strong resistance from the community. The cultural values of mutual cooperation become the argument for rejection and at the same time concern related to the promoting of individualistic values and culture. The problem is, as a country that projects industrialisation as the backbone of the economy, the existence of the Patent Law becomes a necessity. The Patent Law is believed to be the driving force of the industry through technological inventions. The conflict between values of the people's aspirations and the pragmatic policies of the government needs to be compromised and harmonized properly. This research is important to revisit the constellation of politics and legal policy in the establishment of the 1989 Patent Law. The research method is normative and analyze based on the perspective of responsive legal theory and the welfare state. The result of research shows that the preparation of the Patent Law has succeeded in harmonizing substantive patent norms with national interest. The politics of patent law has become the strategy in realizing national goals to build economic power through industrialisation based on technology. This rationality justifies the policy of the need for Indonesia to have a Patent Law in favor of national interests to support industry and economic development.